2021
DOI: 10.1371/journal.pone.0259555
|View full text |Cite
|
Sign up to set email alerts
|

A simulation study of drone delivery of Automated External Defibrillator (AED) in Out of Hospital Cardiac Arrest (OHCA) in the UK

Abstract: Background Drones are increasingly used in healthcare, and feasibility studies of deployment of Automated External Defibrillators (AED) in Out-of-hospital cardiac arrest (OHCA) have been conducted. Despite the potential contribution of drones to healthcare, regulatory barriers exist, including limits on flights beyond visual line-of-sight (BVLOS). The aim of this project was to deliver an AED BVLOS in Wales. Methods We developed of a Concept of Operations (CONOPS) to identify requirements, constraints, organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…This is an answer to an important problem for patients with out-of-hospital cardiac arrest outcomes. 20–23 …”
Section: Discussionmentioning
confidence: 99%
“…This is an answer to an important problem for patients with out-of-hospital cardiac arrest outcomes. 20–23 …”
Section: Discussionmentioning
confidence: 99%
“…Four studies [ 20 , 21 , 22 , 23 ] were conducted in Canada, one [ 24 ] in France, two [ 25 , 26 ] in Germany, five [ 27 , 28 , 29 , 30 , 31 ] in Sweden, two [ 32 , 33 ] in the United Kingdom, one [ 34 ] in Ireland, one [ 35 ] in South Korea and 10 [ 18 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ] in the United States. These locations varied in geographic scale from counties and towns to entire cities and covered a broad range of urban and rural settings.…”
Section: Resultsmentioning
confidence: 99%
“…In Wales the project Concept of Operation was developed, to identify the requirements associated with deploying the drone to deliver ADS beyond visual line-of-sight (BVLOS). Studies showed successful transportation of an ADS by parachute payload drops, final delivery of 4.5 km was completed in 2:50 minutes [19].…”
Section: Delivery Of Adsmentioning
confidence: 99%